Employee turnover in the hospitality industry: A Case study in the Western Province of Zambia - Mukumbuta, Mundia; Ng, Alex, Hou Hong; Lim, Kim Yew; Wong, Chee Hoo (INTI International University, 2019)
The hospitality industry in Zambia is one of the key factor contributing to the country’s economy. However, the industry is faced with high rates of employee turnover. Employee turnover is the number of employees leaving work/employment in one organization for other jobs perceived better. Employee turnover hurts the productivity and financial performance of a company. This study aimed to investigate the factors influencing employee turnover of non-executive employees in the hospitality industry within the Western Province of Zambia. This study adopted a quantitative research design method and questionnaires were used for data collection. The sample size of this study is 273 non-executive employees working in the hospitality industry within the Western Province of Zambia. The research findings revealed that salary, work conditions, incentives, job rotation and long working hours have a significant influence on employee turnover. Few recommendations were provided for future improvements on the employee turnover issues in the hospitality industry within the Western Province of Zambia.